Single dose Intraoperative Antibiotics versus Postoperative Antibiotics for Patient Undergoing Laparoscopic Cholecystectomy for Symptomatic Cholelithiasis: a Randomized Clinical Trial - Thapa, Sagun Bahadur; Kher, Yeshwant Ramakrishna; Tambay, Yashwant Gajanan (Journal of Lumbini Medical College, 2017)
Introduction: Surgical site infection is a common complication shown in literature following cholecystectomies. Smaller incision and use of trocars in laparoscopic cholecystectomy lessen the contamination resulting in less chances of surgical site infection. However, in fear of postoperative infection, many opt for the prolonged postoperative use of antibiotic and there is growing consensus against it. Antibiotics not only increases the cost and hospital stay duration but it aids in emergence of multidrug resistance. Because of the controversies, we conducted this clinical trial to see whether a single prophylactic dose of antibiotic at the time of induction of anesthesia for laparoscopic cholecystectomy was equally effective in controlling post-operative infection as multi-dose antibiotics during and post-operative period. Methods: The study was conducted at the department of general surgery, Lumbini Medical College Teaching Hospital, from November 2015 to October 2016. All cases with symptomatic cholelithiasis subjected for laparoscopic cholecystectomy were enrolled. Patients were randomized into two groups; Group SD received single dose of an intravenous dose of amikacin 500 mg, at induction of anesthesia and Group MD received multiple intravenous dose of amikacin, during and postoperatively for two days. Complications, hospital stay, and treatment cost in two groups were compared and analyzed. Results: There were a total of 240 patients in the study, 118 in Group SD and 122 in Group MD. Post-operative infection rate was 4.2% (n= 5, N=118) in Group SD and 3.3% (n=4, N=122) in Group MD; the difference was not significant (p=0.75). Hospital stay was prolonged and cost was higher significantly in Group MD. Conclusion: Single dose of prophylactic antibiotic, administered at induction of anesthesia, is equally effective as multiple doses of post surgical antibiotics to prevent post-operative infection in patients undergoing elective laparoscopic cholecystectomy for uncomplicated cholelithiasis. Journal of Lumbini medical College Vol 5, No 1, Jan-June 2017, page: 13-17 DOI: https://doi.org/10.22502/jlmc.v5i1.112